ELL2 Is Downregulated and Associated with Galactose-Deficient IgA1 in IgA Nephropathy - Liu, Youxia (Dis Markers, 2019)
BACKGROUND: Galactose-deficient IgA1 (Gd-IgA1) is an important causal factor in IgA nephropathy; however, the underlying mechanism for the production of Gd-IgA1 is unknown. The elongation factor for RNA polymerase II (ELL2), which encoded a key component of the superelongation complex (SEC), drives secretory-specific Ig mRNA production. METHODS: We enrolled 21 patients with IgAN, 18 healthy controls, and 20 patients with non-IgAN glomerulonephritis. The differential expression of ELL2 was compared using publically available data from Gene Expression Omnibus (GEO) datasets. The relationship between ELL2 expressions and galactose-deficient IgA1 (Gd-IgA1) levels in serum were also studied. At last, the results were validated by shELL2 treatment experiment. RESULTS: We found that the number of CD19+ B cells was increased in IgAN patients compared to healthy controls. The expression level of ELL2 in patients with IgAN was significantly lower than that of healthy control and disease control. Consistent with present results, the lower ELL2 expression in IgAN patients was observed in microarray expression profiles from GEO datasets. Pearson correlation analysis showed that ELL2 expression negatively correlated with Gd-IgA1 levels. Furthermore, in an in vitro experiment, we found that loss of ELL2 function in human B lymphoma DAKIKI cells, an IgA1-producing cell line, increased the levels of Gd-IgA1, which confirmed that ELL2 modulated the levels of Gd-IgA1. CONCLUSION: Our findings implied that decreased ELL2 expression was negatively correlated with the numbers of B cells and aberrant glycosylation of IgA1 in IgAN.